4,5-Diiodo-2-phenyl-1H-imidazole - Tomáš Chlupatý; Patrik Pařík; Zdeňka Padělková (Acta Crystallographica Section E, 2012)
The structure of the title compound, C9H6I2N2, contains two symmetry-independent molecules. The interplanar angles between the imidazole and phenyl ring planes are 16.35 (3) and 17.48 (6)°. Molecules are connected via N—H...N hydrogen bonds to form zigzag chains along the b axis. The title compound is the first example of a structurally characterized 4,5-diiodoimidazole with an organic substituent in the 2-position and without protection on the N—H group of imidazole.